2011
DOI: 10.1590/s1726-46342011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de sobrepeso y obesidad en niños menores de cinco años en el Perú 2007-2010

Abstract: RESUMENObjetivos. Estimar la prevalencia de sobrepeso y obesidad en niños menores de cinco años en el Perú durante los años 2007 a 2010 y describir su distribución de acuerdo con ámbitos geográficos, niveles de pobreza, edad, educación de la madre, lactancia materna exclusiva, sexo y peso al nacer. Materiales y métodos: Se realizó una encuesta continua (transversal repetida), por muestreo aleatorio multietápico, del universo de niños menores de cinco años y gestantes residentes en el Perú, dividido en cinco ám… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
3
1
3
Order By: Relevance
“…For example, a population-based study in Peru revealed a much lower prevalence of excess body weight (6.9%) in children under age 5 years, compared to our findings. 29 Conversely, a cross-sectional study in Brazil 30 showed a 30.3% prevalence of excess body weight in adolescents, which is higher than the one we report for that age group. Compared to our study, the official national survey of Mexico 31 revealed a lower prevalence of excess body weight among children aged 5-11 (33.2% vs 41.1%), but a higher prevalence in children aged 12-19 (36.3% vs 23.1%).…”
Section: Discussioncontrasting
confidence: 76%
“…For example, a population-based study in Peru revealed a much lower prevalence of excess body weight (6.9%) in children under age 5 years, compared to our findings. 29 Conversely, a cross-sectional study in Brazil 30 showed a 30.3% prevalence of excess body weight in adolescents, which is higher than the one we report for that age group. Compared to our study, the official national survey of Mexico 31 revealed a lower prevalence of excess body weight among children aged 5-11 (33.2% vs 41.1%), but a higher prevalence in children aged 12-19 (36.3% vs 23.1%).…”
Section: Discussioncontrasting
confidence: 76%
“…Similar analyses from 2007 to 2010 showed that overweight in children under five years was related to: first year of life, male gender, birth weight more than 2.5 kg and living in high urbanized areas (i.e. Lima and the Coast region) [11]. However, these studies lacked of nutrition characterization during the entire period of economic development and social policy enhancement in Peru.…”
Section: Introductionmentioning
confidence: 93%
“…These differences had been described before. For example, it was found in previous studies that, between 2007 and 2010, the highest prevalence of overweight and obesity in Metropolitan Lima was 10.1%, while in the rainforest only 2.6% in children under 5 years [ 26 ] suffered from this problem. Conversely, Tarqui et al [ 27 ] found that, during the period 2007–2011, the coast displayed higher prevalence rates on average than Metropolitan Lima (7.6% vs 7.3%).…”
Section: Discussionmentioning
confidence: 99%